Asymptomatic autoimmune liver disease in scleroderma. Issue 593 (March 1975) - Gupta, M. M.; Warnes, T. W.; Watson, L.
Abstract : A case is described of scleroderma with asymptomatic autoimmune liver disease. The patient presented with the features of CRST syndrome (calcinosis, Raynaud's phenomenon, sclerodactyly and telangiectasia) and a raised plasma alkaline phosphatase was found on routine investigation. It is suggested that this latter biochemical finding is likely to indicate associated autoimmune liver disease in patients with scleroderma.